Embedded Software Unit Dynamic Test Based on C++Test - YANG Ying; LI Wen-bo; ZHONG Li (机车电传动)
Taking on-board auxiliary converter platform software unit dynamic test as an example, embedded software unit dynamic test technology and method based on C++Test tool were expounded, including embedded software unit test environment developing, setting of stub function, test cases programming and executing, and coverage ratio accounting etc, which guided unit test for software designer and tester effectively.